Decorated 6, 6′, 7, 7′-tetrahydro-1H, 1′H-2, 3′-biindole scaffold as promising candidate for recognition of the CDK2 allosteric site. Issue 2 (13th November 2014) - Rescifina, Antonio; Scala, Angela; Sciortino, Maria Teresa; Colao, Ivana; Siracusano, Gabriel; Mazzaglia, Antonino; Chiacchio, Ugo; Grassi, Giovanni
Abstract : Decorated 6, 6′, 7, 7′-tetrahydro-1 H, 1′ H -2, 3′-biindoles, such as DPIT, targeting CDK2 seem to be an attractive scaffold for development of useful anticancer drugs. Abstract : Progression through the S phase of the cell cycle is controlled by cyclin-dependent kinase 2 (CDK2), the activity of which depends on its binding to regulatory partners (cyclins E and A). Deregulation of the activity of CDK2 has been associated with several types of sickness, such as infectious, neurodegenerative, and proliferative diseases. Based on these data, CDK2 has become an attractive target for the development of new anticancer drugs. Indoledione derivatives have recently received special attention in virtue of their pronounced biological effects, such as antiproliferative, antioxidant and antimicrobial properties. In the present work we have investigated the antiproliferative effect of an indolone-based derivative, namely DPIT, whose synthesis we have recently reported, with the aim to clarify its mechanism of action. Furthermore, docking studies have been performed on the eight stereoisomers of DPIT to investigate their capacity to interact as a ligand with ortho - or allosteric sites of CDK2. The encouraging results showed DPIT as a promising candidate for a new type 3 class of inhibitors of CDK2 that recognize the allosteric site.